Implementasi Model Pembelajaran Problem Based Learning Dalam Peningkatan Hasil Belajar Siswa MTs Nur Ibrahimy - Muhammad Rizki Ritonga; Rahmat Idris Hasibuan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to find out whether the application of the Problem Based Learning learning model can improve learning outcomes for class VIII B students at MTs Nur Ibrahimy, totaling 38 students. This research is a classroom action research carried out in two cycles. Each cycle has stages of planning, implementation, observation and reflection. The data collection technique is through tests to determine student learning outcomes using the PBL learning model. The research is considered successful if the average student learning outcome score reaches the KKM, namely 70 with a classical completion percentage of 80%. The results of the research showed that in cycle I the average score obtained by students was 65 with a classical learning completeness percentage of 56% and in cycle II data was obtained on student learning outcomes with an average student score of 77.8 with a classical learning completeness percentage of 89%. Based on these data, it can be concluded that the application of the Problem Based Learning learning model can improve the learning outcomes of class VIII B students at MTs Nur Ibrahimy.